Oocyte Maturity in Relation to Woman's Age in In Vitro Fertilization Cycles Stimulated by Single Regimen - Lee, Hee Jun; Jee, Byung Chul; Suh, Chang Suk; Kim, Seok Hyun; Moon, Shin Yong (Yonsei medical journal, 2012)
During stimulated in vitro fertilization (IVF) cycle, up to 30% of the recovered oocytes are immature ones which have poor fertilization capacity; however, the precise influencing factors are largely unknown. Here, we analyzed the association of oocyte immaturity with woman's age in IVF cycles stimulated by single regimen. A total of one-hundred ninety five IVF cycles stimulated by recombinant FSH and GnRH antagonist protocol between 2003 and 2009 were analyzed retrospectively. The mean age of women was 34.2 ± 4.0 (26-45 years). After triggering by exogenous hCG, an ultrasound-guided retrieval of oocytes was performed 35-36 hours later. All clinical data were stratified by woman's age; group I: ≤ 30 (n=36), II: 31-35 (n=83), III: 36-40 (n=57), and IV: ≥ 41 (n=19). The total retrieved oocytes, as well as immature oocytes, were significantly lower in group IV, however, the mean % of immature oocytes was significantly higher in group IV than other age groups. Oocyte immaturity tended to decrease as increasing age in women aged 40 years or less. In stimulated IVF cycle, much higher oocyte immaturity was noted in women aged 41 years or more.